The cross-appeal appeal - Mohamed Hobby, Assistant Lecturer surah (The college of law and political science journal, 2023)
Our research tagged (Cross-Appeal) came for clarify its meaning andpresentation of the conditions that must be met to follow it, which are representedin the existence of an original appeal, since the cross-appeal should be facing theappellant and to be on the same Judgment of judicial contested by the originalappeal, as well as the existence of a legal interest for the cross-appellant unlessit was His right to appeal has been forfeited as the time has passed or for hisDFFHSWDQFHRIWKHMXGLFLDOUXOLQJDQGWKHVSHFLÀFLW\RIWKHFURVVDSSHDOKDVEHHQFODULÀHGE\GLVWLQJXLVKLQJLWIURPWKHRULJLQDODSSHDODQGWKHVXEVLGLDU\RUDFFHVVRU\appeal .We have favored the adoption of the descriptive approach to research thesubject of the cross-appeal, in particular the study of content analysis, throughwhich it became clear to us that the Iraqi legislator had neglected the organizationof the subsidiary or accessory appeal and the appeal raised by the mediation ofthe original appeal, which prompted us to petition the Iraqi legislator to treat thisLegislative shortage